Review article - Impact of Vitamin K on Human Health - Fakhree, Najwan K.; H. Mhaibes, Sarah; H. Khalil, Heba (Iraqi Journal of Pharmaceutical Sciences, 2021)
Vitamins k is an important fat-soluble vitamin that can be obtained from plants, bacteria and animals and is necessary for the blood clotting. It plays a key function as a cofactor in the synthesizing of blood clotting proteins in the liver; recently, the interest for its functions in extra-hepatic tissue has increased. Vitamin k deficiency is usually caused by abnormal absorption rather than in the lack of vitamin in food. Apart from its impact on clotting, chronic subclinical deficiency of vitamin K maybe a risk factor for many diseases such as osteoporosis, atherosclerosis, cancer, insulin resistance, neurodegenerative diseases and others, while current food intake guidelines be focused on the daily dose necessary to avoid blood loss. Several researchers found out that vitamin K needs may be substantially higher for certain health functions.